The Controlling Nutritional Status (CONUT) Score as a Predictor of Local Recurrence in Patients Underwent Partial Nephrectomy Alongside the R.E.N.A.L. Nephrometry Score - Yorulmaz, Enis Mert; Köse, Osman; Özcan, Serkan; Görgel, Sacit Nuri; Akın, Yiğit (Urology Journal, 2024)
Purpose: This study aims to assess the utility of the CONUT (Controlling Nutritional Status) Score and R.E.N.A.L. (Renal Nephrometry Score) Score in predicting tumor recurrence in patients with kidney cancer. Additionally, we investigated which parameters contributed to these scores. Materials and Methods: In total, 115 patients who underwent partial nephrectomy between January 2015 and August 2023 at a single tertiary center were enrolled. After the exclusion criteria, data from 88 patients were analyzed. Age, gender, body mass index (BMI), comorbidities (hypertension, diabetes), smoking status, tumor characteristics, CONUT Scores, and R.E.N.A.L. scores were retrospectively recorded. Statistical analyses were performed, and significant p was p < 0.05. Results: The presence of diabetes and hypertension showed a statistically significant association with tumor recurrence (p = 0.033 and p = 0.003, respectively). A high BMI significantly increased the risk of recurrence (p < 0.05). There was a strong positive relationship between the high tumor stage and positive surgical margins with recurrence (p < 0.001). Patients with high R.E.N.A.L. Scores and high CONUT Scores had a higher risk of recurrence (42.1% and 8.7%, respectively), and this difference was statistically significant (p < 0.001). Conclusion: CONUT and R.E.N.A.L. scores may be used to predict tumor recurrence after partial nephrectomy. Additionally, diabetes, hypertension, high BMI, and positive surgical margin rate might affect surgical success rate for recurrences. Clinicians should consider all these parameters and coring systems to gather more successful results after partial nephrectomy.